2018
DOI: 10.1007/s10147-018-1299-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and external validation of a nomogram to predict high-grade papillary bladder cancer before first-time transurethral resection of the bladder tumor

Abstract: The present nomogram can help clinicians calculate the probability in patients with bladder cancer before TUR-Bt and decide on earlier intervention and priorities for the treatment of patients diagnosed with bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…A previous study demonstrated that large tumor size was an important risk factor for a multitude of tumors including bladder (17), lung (18), and prostate cancers (19). Our study suggested that patients with larger tumors had a diminished survival as compared to those with smaller size tumors.…”
Section: Discussionsupporting
confidence: 53%
“…A previous study demonstrated that large tumor size was an important risk factor for a multitude of tumors including bladder (17), lung (18), and prostate cancers (19). Our study suggested that patients with larger tumors had a diminished survival as compared to those with smaller size tumors.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, this nomogram was validated by Osawa et al 29 using 834 patients who received radical cystectomy at 21 Japanese institutions, and concluded that Aziz A' nomogram was suitable for both preoperative patient counseling and perioperative care in Europe and Japan. Wakai et al 30 developed and validated a predictive model for predicting high-grade papillary bladder cancer before first-time TURBT based on macrohematuria, tumor size, multiple tumors, appearance, and positive urinary cytology in 424 patients. They also identified number of primary tumors significantly associated with high-grade papillary bladder cancer, which is in accordance with ours.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that large tumor size is an important risk factor for a multitude of tumors including bladder [17] , lung [18] , and prostate cancers [19] . Our study suggested that patients with large tumors had a diminished survival as compared to those with smaller size tumors.…”
Section: Discussionmentioning
confidence: 99%